Implementation of the Methadone Maintenance Therapy Program for Highrisk Drug Prisoners - Moch Subhan Zakaria (Universitas Islam Negeri Walisongo Semarang, 2020)
The harm reduction program is a program that aims to assist inmates who use syringes (IDU's) in overcoming dependence on narcotics medically and to prevent the adverse effects caused by narcotics abuse. Where in general the use of heroin is done by injecting using a syringe alternately, or known as